PERAN GURU DALAM MEMOTIVASI BELAJAR SISWA SD ALKHAIRAAT 03 KAMPUNG MAKASSAR KOTA TERNATE DI MASA PANDEMI - Dian Adinda Puspita; Selvi Wulandari (PEDAGOGIK, 2021)
The purpose of this study was to determine the teacher's role in motivating the learning of SD Alkhairaat 03 Kampung Makassar students during the pandemic and to describe the factors that inhibited student learning motivation at SD Alkhairaat 03 Kampung Makassar, Ternate City. This study uses a qualitative research approach. In collecting data using observation techniques, interviews, and documentation. Respondents in this study were classroom teachers and students. The results showed that the teacher's role in motivating students was maximal, the teacher gave various motivations by (1) giving praise; (2) involving students in the learning process; (3) make class conditions conducive; (4) the use of various learning media. While the inhibiting factors for the lack of student learning motivation during the pandemic are (1) lack of internet access when online learning is implemented; (2) teachers do not really understand how to learn by using online applications; (3) media and learning models that do not vary. Thus it can be concluded that the teacher's role in motivating students' learning at SD Alkhairaat 03 Kampung Makassar, Ternate City is good, but less than optimal because there are still obstacles. Teachers should in the learning process use more varied methods, invite students to learn to take advantage of the surrounding environment.